2014
DOI: 10.1016/j.cattod.2013.10.054
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of water traces on the acidity measurement of amorphous aluminosilicates

Abstract: For the measurement of their acidity, amorphous aluminosilicates are beforehand treated at temperature of 450°C or higher in order to remove water adsorbed on their surface. We will show in this study that, during the standard course of an acidity measurement by low temperature CO adsorption, traces of water present in the setup may perturb the acidity measurement by desorbing from the setup and adsorbing on the sample. We will also demonstrate that the interaction of water occurs on mild and strong Lewis site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… It was reported that in amorphous silica–alumina, water molecules adsorbed on aluminum atoms and interacting with neighboring silanols can easily be deprotonated and, therefore, are Brønsted acidic sites . Thus in MSH, magnesium may polarize adsorbed water and form Brønsted acidic sites (Figure a and b), which could stabilize the methoxide molecule, or activate ester, directly by bonding to the carbonyl group, or indirectly, favoring the departure of the alkoxyl group as reported by Greenwell et al.…”
Section: Resultsmentioning
confidence: 79%
“… It was reported that in amorphous silica–alumina, water molecules adsorbed on aluminum atoms and interacting with neighboring silanols can easily be deprotonated and, therefore, are Brønsted acidic sites . Thus in MSH, magnesium may polarize adsorbed water and form Brønsted acidic sites (Figure a and b), which could stabilize the methoxide molecule, or activate ester, directly by bonding to the carbonyl group, or indirectly, favoring the departure of the alkoxyl group as reported by Greenwell et al.…”
Section: Resultsmentioning
confidence: 79%
“…This can tentatively be attributed to some in situ modifications of the strongest Lewis acid sites in 16Si-1Al-Ac-T, possibly under the action of water. [65,74] HZSM-5 deactivation was presumably caused by coke deposition due to the presence of strong Brønsted acid sites promoting ethylene oligomerization. [16,17,21,22] This suggestion can be supported by several observations: (i) HZSM-5 produced small amounts of acetaldehyde, propene, and butenes (these molecules are easily oligomerized/polymerized); (ii) fresh HZSM-5 was totally white spent HZSM-5 was pale brown; (iii) the pore volume decreased by 26 % (N 2 physisorption, Table 3S); (iv) a weak band was observed in Raman spectra of spent HZSM-5 at ca.…”
Section: Catalyst Stability At Maximum Productivitymentioning
confidence: 99%
“…40 This is also in agreement with experimental observations according to which water molecules on ASA contribute to the Brønsted acidity of these. 77,[336][337] Generally speaking, the stabilization of the conjugated base of the acid site, and of the protonated probe molecules (i.e., the products of the proton transfer reaction) appeared to be key for the expression of Brønsted acidity of ASA. Whereas these factors also play the role in and on zeolites, 39 the acidity ranking of Al-(H 2 O) versus bridging OH groups at the external surface of ZSM-5 appeared to be dominated by the intrinsically lower acidity of these two sites.…”
Section: Acidity Of Surface Oh Groups On Asamentioning
confidence: 99%